Qorpo-Santo, Zé Limeira e Campos de Carvalho à luz do absurdo - Brito, Mariana Fernandes (2018)
We investigate the absurd from its meanings, trying to describe its concept systematically to observe it in the Brazilian Literature, from the mid-nineteenth century throughout the twentieth century, however, with emphasis on three authors in three literary genres. There isn’t a line in this perspective in the Brazilian Literary Studies. We proposed to ally conceptually about the absurd these authors: Aristotle, Nietzsche, Bakhtin, Deleuze, Camus, Umberto Eco, Antonio Candido, Hobsbawm, Italo Calvino, Szondi, Sartre, Décio Pignatari, Auerbach and Martin Esslin andmore. From this, we observe the absurd in the Brazilian Literature, despite the restriction to three authors. We couldn’t rely only on the critical fortune and theory developed by Brazilian authors about the absurd, so we had to resort to foreign authorship to use them. In this way, we join Nietszche in the same scenario with Hobsbawm and Antonio Candido, in a philosophical and historical sense regarding Modernity as an object of observation. In parallel, we employ Bakhtin, approaching Rabelais, and we resort to Aristotle, still about the setting, providing theoretical and archaeological bases for the discussion of literary genres and the grotesque hybridism of styles in association with the absurd. We know, from the deferred names, what underlies our subjectivity, our history and our way of living, that our choices are direct consequences of the twentieth century. In this, we pointed to the reflexive question of the absurd, using those who dedicated much to it.Sartre and Camus serve as basis for existential and, more specifically, absurd reasoning, respectively, and Calvino illustrates them quite punctually. We also start from the relationship between these three to discuss some meanings, while countering the false understanding that the absurd is an original creation and belonging to France, even one of the authors of the corpus serves as a contestation: Qorpo-Santo.This writer not only anticipates what a hundred years later we would call the Theater of the Absurd, marking Brazil on the map of the subterranean current where the absurd lives and its authorships representatives, but also shares a considerable difficulty in trying to become recognized, with the other two authors: Zé Limeira and Campos de Carvalho. The first had to dribble its illiteracy, its status of anonymous, the isolation of the Northeastern backlands and other factors, to become the myth of Paraiba that he is today. Campos de Carvalho emerges from decades to decades, and cannot achieve more than the alternative current of Brazilian Literary Studies. Certainly, after some time since the launch of his works, we can already consider him an author recognized, in a way, but still of countercurrent. In general, these three names, respectively in drama, in poetry and in novel, inhabit the underworld to which all authorship chooses to expose or express uncomfortable ideas, as is the lack of meaning that exists in everything, in order to say, according to the principles of pataphysics formulated by Albert Jarry, that (or almost) nothing is serious, just as seriousness can be treated in a humorous way.